Researching Policy and Practice to Safeguard People With Intellectual Disabilities from Abuse: Some Methodological Challenges. Issue 3 (10th September 2013) - Northway, Ruth; Jenkins, Robert; Jones, Victoria; Howarth, Joyce; Hodges, Zoe
Abstract: Abuse of adults with intellectual disabilities can and does occur in many places, and as a result, many countries have instituted policies and enacted laws to address this problem. However, research concerning the impact of such policies on abuse remains largely limited to quantitative studies from the perspective of governmental or other authorities and is generally focused on one area or country. Absent are the views and experiences of people with intellectual disabilities with respect to real or perceived abuse. Given the dearth of research involving primary consumers, there is limited knowledge as to the success or failure of such policies and laws. Though carrying out such research can pose methodological and ethical challenges, not undertaking it can also have ethical and social consequences. An international research agenda that includes participatory research that both facilitates the active involvement of and investment in people with intellectual disabilities and views action as an essential outcome is thus proposed. The authors propose such an agenda and posit that along with the collection and analysis of substantially more robust quantitative data, this should facilitate comparison within and between countries.